Analytical Methods for the Identification of Edible and Feed Insects: Focus on DNA-Based Techniques - Zdeňková, Kamila; Čermáková, Eliška; Vejl, Pavel; Čermáková, Agáta; Vašek, Jakub (Foods (Basel, Switzerland), 2025)
The utilization of insects as a source of essential nutrients holds considerable promise, with the potential to serve as both feed and food. Consequently, there is a necessity to develop control systems, as the undeclared addition of insects to food products and/or non-compliance with labelling regulations may pose health risks and result in financial losses for consumers. This review describes methods for identifying and detecting insect species by targeting biomolecules such as DNA, proteins, saccharides, and metabolites, with a particular focus on DNA-based approaches. This review provides a detailed overview of the application of polymerase chain reaction (PCR) and DNA sequencing methods that are suitable for the analysis of edible and forage insects. The main focus is on identifying species that are approved for use as novel foods or insect feeds within the European Union (e.g., house cricket (Acheta domesticus), common mealworm (Tenebrio molitor), migratory locust (Locusta migratoria), lesser mealworm (Alphitobius diaperinus), black soldier fly (Hermetia illucens), banded cricket (Gryllodes sigillatus), field cricket (Gryllus assimilis), silkworm (Bombyx mori)). However, insect species of global relevance are also discussed. The suitability of DNA analysis methods for accurate species identification, detection of (un)labeled contaminants, and monitoring of genetic diversity has been demonstrated.
Keywords: sequencing; PCR; insect species identification; DNA barcoding; edible insect